THE ROLE AND IMPORTANCE OF EDUCATIONAL TECHNOLOGIES IN IMPROVING THE PERSONAL AND PROFESSIONAL QUALITIES OF FUTURE PHYSICAL EDUCATION TEACHERS - Ulugbek Rakhmonov Normahmatovich (Galaxy International Interdisciplinary Research Journal, 2022)
From the first days of independence, Uzbekistan has paid great attention to the development of physical culture and sports, the promotion of a healthy lifestyle. Raising a harmoniously developed young generation has been identified as one of the priorities of state policy. A number of decrees and resolutions have been adopted in this regard. The large-scale work carried out in our country places a great responsibility on the professors and coaches of the departments of physical culture and sports of the higher education institution. Physical culture and sports help to prepare young people for life, socially useful work, to improve their physical abilities, to prepare them for the defense of the Motherland, to help them develop to perfection.